Evaluation of chemoprotective effects of Phyllanthus niruri against azoxymethane-induced foci of aberrant crypts in rats / Halabi Mohammed Farouq O. - Halabi, Mohammed Farouq O (2012)
Phyllanthus niruri (P. niruri) is an important Malaysian medicinal plant commonly used traditionally for the treatment of many aliments. The present investigation was designed to elucidate the chemoprotective effects of ethanolic extract of this plant against azoxymethane-induced (AOM) foci of aberrant crypts in rats. Sprague Dawley rats received injections of AOM (15mg/kg, once weekly) for two weeks. Daily treatments with P. niruri extracted, 250mg/kg and 500 mg/kg of body weight as low and high dose, respectively, were orally administered for eight weeks. At the end of the study, aberrant crypt foci (ACF) were evaluated and examined under a light. The numbers of crypts per focus and liver functions tests were also done in serum (biochemical parameters). P. niruri was found to be effectively chemoprotective, as evidenced microscopily and biochemicall. Pre-treatment with P. niruri ethanolic extract, significantly reduced the impact of AOM toxicity on plasma protein and urea levels as well as on plasma aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH) and gamma-glutamyl transpeptidase (GGT) activities. Grossly, colorectal specimens revealed that ethanol extract of P. niruri treatments decreased the mean score of number of crypts in AOM-treated rats. Acute toxicity test did not show any signs of toxicity and mortality up to 5 g/kg. In conclusion, the current study demonstrated that ethanolic extract of this plant slowed reduction of ACF. According to these data, P. niruri might be a promising chemoprotective activity, suggesting the need to isolate the chemical principles responsible for this activity and to study this activity in a model of AOM-induced in ACF.